The Development of Learning Material for Seminar on English Language Teaching Course Based on Flipped Learning - Masitowarni Siregar; Nora Ronita Dewi; Safrida Lubis (BIRCU, 2020)
This study amis at establishing instructional material for the Subject of Seminar on English Language Teaching based on Flipped Learninng. In English Educational Study Program fifth semester students students of English Educational Study Program, FBS, UNIMED. The study was conducted by utilizing Research and Developmental Study There were three phases realized in this study: : First Survey and Evaluation Phase, second designing the material and finally validating theinstructional material. Based on the phases of the study followed, the following topics of instructional material were developed ; Foundation of Seminars, Some Key Terms s of Seminars and Paper Presentations, Analyzin Topics for Seminar , Working out Pertinant Topics, Establising Paper Outline, Writing Paper Draft, Editing and Finalizing Paper, Designing Paper Presentations, Developing Power Point Presentation, Rehearsing Presentation, Paper Presentation, Running Productive Seminar. The feasibility test of teaching materials by the specialist. The findings indicated that theoutcome of the study established were suitable pertinent and fit in with the students of English Education Study Program with the mean 4.32.The material was upload to E-Learning FBS UNIMED to be utilized by the students.